1999
DOI: 10.1038/sj.bmt.1701953
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of transplant-related mortality (TRM) after allogeneic bone marrow transplants (BMT): blood urea nitrogen (BUN) and bilirubin

Abstract: Summary:Transplant-related mortality (TRM) following allogeneic bone marrow transplantation (BMT) remains a major concern and early identification of patients at risk may be clinically relevant. In this study we describe a predictive score based on bilirubin and blood urea nitrogen (BUN) levels on day +7 after BMT. The patient population consisted of 309 consecutive patients who underwent BMT from sibling (n = 263) or unrelated donors (n = 46) for hematologic disorders between December 1990 and December 1996. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 17 publications
1
26
0
1
Order By: Relevance
“…In a recent study including more than 300 patients, it was found that relatively small increases in bilirubin and blood urea nitrogen on day 7 after transplant increased the 100-day TRM from 10% to 28%. 6 Patients with a high risk score died more often of AGVHD, infections and multi-organ failure. In our study, almost 50% of MTC were VOD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study including more than 300 patients, it was found that relatively small increases in bilirubin and blood urea nitrogen on day 7 after transplant increased the 100-day TRM from 10% to 28%. 6 Patients with a high risk score died more often of AGVHD, infections and multi-organ failure. In our study, almost 50% of MTC were VOD.…”
Section: Discussionmentioning
confidence: 99%
“…5 Also, an early increase in serum bilirubin and/or blood urea nitrogen (BUN) after BMT has been associated with TRM. 6 Tissue damage can lead to a systemic inflammatory response. C-reactive protein (CRP) is an acute phase protein produced by hepatocytes and is a reliable marker of systemic inflammation.…”
mentioning
confidence: 99%
“…Developing a strategy for pre-emptive intervention against acute GVHD is more difficult to achieve, given the inherent treatment of some patients who would not have developed disease. In 1999, Bacigalupo et al 48 used a clinical scoring system, measured at day þ 7 after HCT, to predict risk of both acute GVHD and TRM. A pilot study in 18 patients followed, which treated highrisk patients with pre-emptive anti-thymocyte globulin, 49 and this clinical scoring system was then refined to include day þ 7 serum levels of BUN, cholinesterase, total proteins, gamma glutamyl transferase, along with donor type and cell dose.…”
Section: Biomarkers For Acute Gvhd Y-b Chen and Cs Cutlermentioning
confidence: 99%
“…However, one first needs to identify patients at risk of GVHD soon after transplant, and with this aim, we worked on a scoring system on day þ 7 after HSCT, first based on day þ 7 bilirubin and blood urea nitrogen. 12 These two laboratory tests identify patients with a significantly different risk of GVHD and transplantrelated mortality (TRM), as shown in our Unit of adult transplants and validated in a separate pediatric Unit using a different central lab. 12 The next step was to test whether an early intervention with immunosuppression was feasible and whether it would reduce severe acute GVHD: we ran a small pilot study with ATG 1.25 mg/kg 3 Â starting on day þ 7, in 18 high-risk patients, and compared the results with a historic group of 20 untreated high-risk patients (controls), and showed reduced acute GVHD in patients receiving the additional dose of ATG on day þ 7.…”
Section: Introductionmentioning
confidence: 96%
“…12 These two laboratory tests identify patients with a significantly different risk of GVHD and transplantrelated mortality (TRM), as shown in our Unit of adult transplants and validated in a separate pediatric Unit using a different central lab. 12 The next step was to test whether an early intervention with immunosuppression was feasible and whether it would reduce severe acute GVHD: we ran a small pilot study with ATG 1.25 mg/kg 3 Â starting on day þ 7, in 18 high-risk patients, and compared the results with a historic group of 20 untreated high-risk patients (controls), and showed reduced acute GVHD in patients receiving the additional dose of ATG on day þ 7. 13 We were in the meantime refining the scoring system on day þ 7, and found other significant laboratory tests such as serum cholinesterase, total serum proteins and gamma glutamyl transferase: 14 the revised day þ 7 score identifies patients with a low risk (15%), an intermediate risk (40%) and a high risk of TRM (60%).…”
Section: Introductionmentioning
confidence: 96%